# How to cite theorems within a series of equations?

I want to know if it's possible to cite theorems within series of equations, without interleaving text like "From Theorem 1.3, it follows that:". Here's an idea of the kind of formatting I'm looking for:

x = 1                                                (Theorem 1.1)
x^2 = 1                                              (Theorem 1.2)
x^2 - 1 = 0                                          (Theorem 1.3)
(x + 1)(x - 1) = 0                                   (Theorem 1.4)
x + 1 = 0                                            (Theorem 1.5)
1 + 1 = 0                                            (Theorem 1.6)
2 = 0                                                (Theorem 1.7)


I also want to be able to do this in a single long, chained equation. e.g. Intermixing it with the align* environment from amsmath:

expr1 = expr2                                        (Theorem 2.1)
= expr3                                        (Theorem 2.2)
= expr4                                        (Theorem 2.3)
= expr5                                        (Theorem 2.4)
= ...


Is it possible to achieve this?

• Yes it works. You can the the flalign environment for this, with the first column empty, the equations in the second column and the references in the last column. – Bernard Nov 1 '17 at 22:26
• @Bernard Sounds great. Can you provide an example via an answer? – James Ko Nov 1 '17 at 22:40

Here are 3 possible layouts for references. alignat gives you full control on the spacing between the equations and the reference, whereas flalign puts references at the right margin:

\documentclass{article}
\usepackage[utf8]{inputenc}
\usepackage[T1]{fontenc}
\usepackage{fourier}
\usepackage{mathtools}
\usepackage[standard, amsmath, thmmarks]{ntheorem}
\usepackage{cleveref}

\begin{document}
\begin{theorem}\label{th:P}
A powerful theorem.
\end{theorem}

\begin{theorem}\label{th:PP}
Another powerful theorem.
\end{theorem}

\begin{flalign}
& & a + b & = c + d + e& & \text{(by \cref{th:P})}\\
& & a' + b' + e'& = c'+ d' & & \text{(by \cref{th:PP})}
\end{flalign}

\begin{align}
a' + b' + e' & = c' + d' & & \text{(by \cref{th:PP})} \\
a + b & = c + d + e & & \text{(by \cref{th:P})}
\end{align}

\begin{alignat}{2}
a' + b' + e' & = c' + d' & \qquad & \text{(by \cref{th:PP})} \\
a + b & = c + d + e & & \text{(by \cref{th:P})}
\end{alignat}

\end{document} 